Parents' perceptions of food intolerance among under-five children in Gianyar Bali - Endy P Prawirohartono; Ni Made Yuni Gumala (Indonesian Pediatric Society Publishing House, 2016)
Objective To estimate the proportion of food intolerance in chil- dren based on parents' perception and to analyze factors associ- ated with food elimination. Methods A cross-sectional study was done among 250 mothers of under-five children in Gianyar District, Bali. Mothers were inter- viewed with a questionnaire concerning basic characteristics of the children, the family, a list of allergic diseases, disturbance after ingesting certain foods, food avoidance, the reason for eliminating certain foods, the person who gave advice, and probable parental history of allergic diseases. Results Fifty-three children (21.2%) were suspected to have 'prob- able allergic diseases' and six (2.4%) had 'probable food intoler- ance'. Food elimination was practiced in 27 (10.8%) families. 'Prob- able allergic parents' was found in 49 (19.6%) families. There was a significant difference in child allergy in proportion to parental allergy (x 2 test p<0.0001). Food elimination was not associated with parental allergies, children's allergies or children's ages (x 2 test p=0.36, 0.47, and 0.56), but seemed to be related to low educational status of mothers (x 2 test p<0.0001) and fathers (Fisher's exact tests p< 0.0001). Conclusions The proportion of children with 'probable allergic dis- eases' was higher in families with 'probable allergic parents'. The proportion of food elimination was greater than the prevalence of 'probable food intolerance'. Low educational status of parents played an important role in this discrepancy of food elimination in children